Palamizm a ikona - Sprutta, Justyna (Poznańskie Studia Teologiczne, 2010)
The theory of hesychasm which was systematized in the 14th century by St. Gregory Palamas is known as Palamism. Palamism focused on the problem of God’s essence and energies, claiming among others that God allows Himself to be known only through His energies whereas His essence remains unknown and is beyond any cognition. Divine energies are represented by an omnipresent supernatural light, expressed in icons by such colours as gold, pure yellow or white. This light is also sometimes indicated by the colour of the assist or the filling of the background and the nimbus. The icon that explicitly expresses and presents the transformation effected by Divine energies is The Transfiguration o f Christ although in fact every icon is meant to lead to transformation. Palamism originated from a controversy between the monk Barlaam and St. Gregory Palamas.